2018
DOI: 10.1007/s12223-018-0601-8
|View full text |Cite
|
Sign up to set email alerts
|

Autolytic hydrolases affect sexual and asexual development of Aspergillus nidulans

Abstract: Radial growth, asexual sporulation, and cleistothecia formation as well as extracellular chitinase and proteinase formation of Aspergillus nidulans were monitored in surface cultures in order to study the physiological role of extracellular hydrolase production in carbon-stressed cultures. We set up carbon-stressed and carbon-overfed experimental conditions by varying the starting glucose concentration within the range of 2.5 and 40 g/L. Glucose starvation induced radial growth and hydrolase production and enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(68 reference statements)
2
2
0
Order By: Relevance
“…With this activity, AnAFP thus contributes to the survival of A. niger . This hypothesis is supported by publications from others who demonstrated that asexual sporulation of A. nidulans is accompanied by autolytic and apoptotic processes [ 53 , 54 , 55 , 56 ]. It is also in agreement with the observation that there is a considerable delay between induction of anafp gene expression and detection of AnAFP in the culture supernatant of A. niger [ 44 , 57 ].…”
Section: Gene Regulation Of Afp-encoding Genes: From the General Tsupporting
confidence: 59%
“…With this activity, AnAFP thus contributes to the survival of A. niger . This hypothesis is supported by publications from others who demonstrated that asexual sporulation of A. nidulans is accompanied by autolytic and apoptotic processes [ 53 , 54 , 55 , 56 ]. It is also in agreement with the observation that there is a considerable delay between induction of anafp gene expression and detection of AnAFP in the culture supernatant of A. niger [ 44 , 57 ].…”
Section: Gene Regulation Of Afp-encoding Genes: From the General Tsupporting
confidence: 59%
“…We propose that young hyphae of A. niger mainly work as nutrient scavengers, having a highly active and compact cytoplasm, whereas old hyphae are important in setting the biofilm's three-dimensional structure, where only the cell wall is needed and thus the cytoplasm appears empty. Mature fungal colonies have been reported to be composed of both metabolic active, metabolic inactive as well as dead hyphae, the latter of which develop through autophagy (Boswell and Hopkins, 2008;Krijgsheld et al, 2013, Emri et al, 2018Kaur and Punekar, 2019;Khalid et al, 2019;Lingo et al, 2021). Our study supports these observations and further highlights that young hyphae at the edge of the colony are not significantly covered by an extracellular matrix.…”
Section: Discussionsupporting
confidence: 87%
“…The production of extracellular autolytic enzymes such as chitinase and glucanase is induced by carbon starvation in A. nidulans (43). Intriguingly, the strain defective in both chiB and engA produced fewer conidia on medium containing low concentrations of glucose (44). This observation indicates that autolysis contributes to the supply of…”
Section: Figmentioning
confidence: 97%